New Media in Teaching UML in the Large — an Experience Report - Brandsteidl, Marion; Wieland, Konrad; Huemer, Christian (Electronic Communications of the EASST, 2011)
Huge classes with more than 800 students pose a major challenge to lecturers as well as to students, especially when a practical part is included. In order to successfully master lectures of this size, novel kinds of teaching media provide a multitude of enhanced opportunities. In this paper, we present our experiences with the application of new media in our undergraduate course Introduction to Object-Oriented Modeling (OOM). In this course, we teach approximately 800-1000 students per year the principles and techniques of UML 2.0. New media, i.e., technologies other than the traditional blackboard presentation like a document camera, web-based self assessments, or lecture recordings, are applied to support both, students and lecturers when learning and teaching, respectively. We empirically underline the acceptance of our concept with the feedback of our students concerning the newly used technologies gained through an extensive survey.